Response of Roses (Rosa hybrida L. ‘Herbert Stevens’) to Foliar Application of Polyamines on Root Development, Flowering, Photosynthetic Pigments, Antioxidant Enzymes Activity and NPK - Yousefi, Fereshteh; Jabbarzadeh, Zohreh; Amiri, Jafar; Rasouli-Sadaghiani, Mir Hassan (Scientific reports, 2019)
The effect of foliar application of polyamines on roses ( Rosa hybrida cv. ‘Herbert Stevens’) was investigated in a factorial experiment based on a completely randomized design with three replications in a greenhouse. Two factors were applied including polyamine type (putrescine, spermidine, and spermine) and polyamine concentration (0, 1, 2 and 4 mM). The recorded traits included root fresh and dry weight, root length, number of flowers, flower longevity, chlorophyll content, carotenoids, antioxidant enzymes activity (catalase, ascorbate peroxidase and guaiacol peroxidase) and some macronutrients such as nitrogen, phosphorus and potassium. The results showed that among polyamines, putrescine had the greatest effect on root dry weight; spermidine showed the greatest effect on root length, chlorophyll content, plant phosphorus and spermine affected root fresh weight and flower longevity most strongly. Polyamine concentration of 1 mM had the strongest effect on flower longevity, carotenoids, nitrogen and phosphorus content. The highest potassium rate was observed in treatments with the concentration of 4 mM. Polyamine treatments had no significant effect on the number of flowers per plant and antioxidant enzymes.